An Interpretative Phenomenological Analysis of the Experience of Ex-Gang Members as They Transition into and Out of Gangs. Issue 2 (15th March 2022) - Bolger, Laura; Needs, Adrian
ABSTRACT: To the extent that existing gang research is grounded predominantly in quantitative methodology, the subjective and retrospective experience of gang members is often overlooked. With this in mind, the present study adopts a qualitative approach to explore the individual trajectories of gang members, illuminating the psychological processes associated with change to develop understanding of gang membership, identity and desistance. The narratives of five ex-gang members were analyzed using interpretative phenomenological analysis to explore their experiences as they transitioned in and out of the gang. Superordinate themes of "Positioning self in a social world, " "Solutions to identity, meaning and belonging, " and "Catalysts for change" shed light on the similarities and divergence across their experience and are discussed in respect of existing literature. Implications for policy, practice and future research are discussed.